Anticancer Activity Of Plant Genus Clerodendrum (Lamiaceae): A Review - Donald Emilio Kalonio; Rini Hendriani; Elisabeth N. Barung (Majalah Obat Tradisional, 2017)
Plants of the genus Clerodendrum (Lamiaceae) is widespread in tropical and subtropical regions. Plants of this genus are used both empirically and scientifically as anti-inflammatory, antidiabetic, antimalarial, antiviral, antihypertensive, hypolipidemic, antioxidant, and antitumor. Results of the molecular docking simulation of chemical content of these plants could potentially provide an anticancer effect. This paper aims to review the anticancer activity of plant genus Clerodendrum based on scientific data. The method used in this study is the literature study. Searches were conducted online (in the database PubMed, Science Direct and Google Scholar) and on various books (Farmakope Herbal Indonesia and PROSEA). A total 12 plants of the genus Clerodendrum have anticancer activity in vitro and in vivo, thus potentially to be developed as a source of new active compounds with anticancer activity.